Judicial reasoning and discretion in underage marriage dispensation cases: a case study from the sumbawa religious court - Maemunah, Maemunah; Isnaini, Isnaini; Akbar, Refli Ahmad; Sakban, Abdul (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
This study examines the judicial considerations in granting underage marriage dispensations at the Religious Court of Sumbawa, Indonesia, a region where early marriage persists despite national legal reforms. The research aims to understand how judges interpret the principle of the child's best interest within a socio-religious legal context. Using a qualitative socio-legal approach, data were collected through courtroom observations, document analysis, and in-depth interviews with judges and petitioners. Findings indicate that although the number of applications has declined between 2022 and 2024, the approval rate remains above 95%, reflecting the powerful influence of social pressures, religious morality, and pragmatic reasoning. Judges frequently invoke maslahah (public good), emotional maturity, and family consensus to justify approval, often prioritizing immediate social stability over long-term child welfare. Judicial reasoning tends to be dialogic and compassionate, but procedural inconsistency and the absence of post-decision support compromise the protective aims of the law. The study highlights the role of legal pluralism in shaping judicial discretion, where Islamic and statutory principles coexist and sometimes conflict. It calls for institutionalizing child-centered procedures, standardized psychosocial assessments, and follow-up mechanisms. These findings contribute to the growing body of literature on child marriage, legal reform, and the role of religion in family law adjudication in Southeast Asia